Aqueous two-phase systems based on cholinium ionic liquids for the recovery of ferulic and p-coumaric acids from rice husk hydrolysate - Lucía Xavier; Mauro Rocha; Justina Pisani; Berta Zecchi (Applied Food Research, 2024)
ABSTRACT: Rice husk (RH) is an abundant agro-industrial residue in Uruguay, being the disposal of it an environmental problem because of the pollution it generates. This work had as objective the obtention of phenolic compounds from RH by alkaline hydrolysis and their separation by means of aqueous two-phase systems (ATPS). An experimental design was implemented for the alkaline delignification process, studying the influence of temperature, solid/liquid (S/L) ratio and NaOH concentration on the hydrolysis yield (HY), total phenolic content (TPC), the antioxidant capacity (FRAP and TEAC) and the ferulic and p-coumaric acids content of the hydrolysates. The optimal conditions were 120 °C, S/L ratio 1/30 g/mL and 2 N NaOH. Subsequently, ATPS based on choline chloride and different surfactants, Tween 20 (Tw20) and Tween 80 (Tw80), were used to separate the phenolic compounds from the hydrolysate. The influence of the tie-line length (TLL), volume ratio (VR) and temperature were studied. Ferulic acid and p-coumaric acid migrated to the surfactant rich-phase in all cases. Systems containing Tw80 turned out to have better separation yields (SY), greater than 90%, for both phenolic acids. SY was not affected by use of different TLL and temperatures, although it was affected by changes on VR.